She's not there : a novel - Fielding, Joy (New York : Ballantine Books, 2016)
"A vanished child, a family in turmoil, and a fateful phone call that brings the torments of the past into the harrowing present. the New York Times bestselling author of Someone Is Watching weaves these spellbinding elements into a gripping novel of psychological suspense--a must-read for fans of Laura Lippman and Mary Higgins Clark. "I think my real name is Samantha. I think I'm your daughter." Caroline Shipley's heart nearly stops when she hears those words from the voice on the other end of the phone. Instantly, she's thrust fifteen years into the past, to a posh resort in Baja, Mexico--and the fateful night her world collapsed. The trip is supposed to be a celebration. Caroline's husband, Hunter, convinces her to leave their two young daughters, Michelle and Samantha, alone in their hotel suite while the couple enjoys an anniversary dinner in the restaurant downstairs. But returning afterward, Caroline and Hunter make a horrifying discovery: Two-year-old Samantha has vanished without a trace. What follows are days, weeks, and years of anguish for Caroline. She's tormented by media attention that has branded her a cold, incompetent mother, while she struggles to save her marriage. Caroline also has to deal with the demands of her needy elder daughter, Michelle, who is driven to cope in dangerous ways. Through it all, Caroline desperately clings to the hope that Samantha will someday be found--only to be stung again and again by cruel reality. Plunged back into the still-raw heartbreak of her daughter's disappearance, and the suspicions and inconsistencies surrounding a case long gone cold, Caroline doesn't know whom or what to believe. The only thing she can be sure of is that someone is fiercely determined to hide the truth of what happened to Samantha. Praise for Joy Fielding's Someone Is Watching "Someone Is Watching gripped me from the first to the very last page. Bailey Carpenter is a heroine who's both victim and warrior woman, a fascinating sleuth who will linger with you long after you've finished this thrilling read."--Tess Gerritsen "Fielding pens a spiraling tale of paranoia and suspense, as sultry as a Miami night."--Jenny Milchman "An edge-of-your-seat read. With Fielding's patented blend of complex characters and escalating suspense, she is in top form here."--Karen Robards "Engrossing. The characters pulsate with life."--Publishers Weekly (starred review) "A gripping, fast-paced psychological thriller. Fielding's story of one woman's search for justice, understanding, and internal peace is nothing short of arresting."--Booklist (starred review)"--
"A lifetime ago, every year Carole Shipley looked forward to her wedding anniversary. But then a celebratory trip to Mexico for the occasion with her husband and friends ended in the unsolved kidnapping of her infant daughter, Samantha. Now, fifteen years after that horrific time, divorced and isolated, Carole is forced to relive the kidnapping by reporters who call every year on the anniversary of Samantha's disappearance. However, this year when the phone rings, Carole hears the sweet voice of a girl claiming to be her long-lost daughter. Plunged back into the world of heartbreak, suspicion and questions that led the case to run cold so many years ago, Carole doesn't know what or who to believe. But when she starts to figure it out, she finds the answers dangerously close to home"--
Booklist
Kirkus Reviews
Library Journal Prepub Alert
Keywords: Mothers and daughters -- Fiction; African Americans -- Fiction; Missing children -- Fiction; Psychological fiction; Suspense fiction; Mystery fiction